Face mist Formulation From Yellow Pumpkin (Cucurbita moschata) Extract as An Antioxidant - La Sakka; Hasma Hasma (Indonesian Journal of Pharmaceutical Education, 2023)
Pumpkin fruit (Cucurbita moschata) is a fruit that contains many benefits for the body, one of which is being able to boost the immune system and having a strong antioxidant content. Face mist is included in skin-refreshing cosmetics that can refresh facial skin, and remove residual oil on the skin. The advantage of this face mist preparation is that it can be easily used and practical to carry anywhere and can quickly seep into the face. This study aims to formulate pumpkin fruit extract into preparations in the form of face mist by carrying out several product analysis processes including organoleptic tests, pH tests, spreadability test and dry time tests so that we can determine the concentrations of face mist preparations that meet the requirements. This research began with the manufacture of pumpkin Simplicia with the drying process after which the pumpkin fruit extract was prepared by maceration method using 70% ethanol to obtain a thick extract. The population and sample in this study are in the Moncongloe area, Paccellekang Village, Maros, South Sulawesi Province. This type of research is experimental research in the laboratory by making 3 formulas consisting of F1 with a concentration of pumpkin fruit extract as much as (1.5 gr), F2 (2 gr), and F3 (2.5 gr). Based on the results of the study it can be concluded that formula F1 and formula F2 are the best formulas because they meet the requirements of SNI standards which are safe and good for use on the skin. Researchers' suggestions for further research are expected to add some product analysis tests on face mist preparations from pumpkin fruit extract.